Social Skills Assessment and Suggested Intervention Plan in a Teenager with William Syndrome (British Journal of Multidisciplinary and Advanced Studies, 2023)
Williams Syndrome (WS) is a neurodevelopmental disorder which can affect equally both genders. It is a genetic disorder which is associated with hemideletion of 28 genes on chromosome 7q11.23. In our case, we have a 16-year-old girl with WS who engages to inappropriate social behavior (i.e., inappropriate contact). The purpose of this assignment is to analyze the assessment data and based on them, propose and implement effective and individualized treatment strategies to prevent and decrease the occurrence of the target behavior. Part of this research study is also to provide mediator training to the teacher.